Letter (copy) : Fondo de Solidaridad Internacional - Santiago, Enrique
030-0197-001 COPY. COMITE ESPANOL. FONDO de SOLIDARIDAD INTERNACIONAL. Aragon, 300. Barcelona 2/3/1938. Sra Gwendolyn Adams de Puertas, 17, Fleet Street, Londres, E.C.4. Dear Madam, I beg to acknowledge your letter of 26th February. I am enclosing a letter, a copy of similar ones that have been sent to Factories that are doing war work, and you will see that food is given to these workers that are working under great strain. We have just distributed 67,000 rations of a ½ kilo of sugar and we shall always try to distribute amongst them the food we are able to get. One of the things that is very appreciated amongst Spanish people is Salt Cod, and if it were possible to obtain some tons of this for the workmen, believe me, it would be helping them very greatly, who are living under great difficulties. The children merit every attention possible, but also these workmen merit alimentation that to-day is unobtainable. Besides this distribution of sugar, we have sent Two Wagons to the Presidente of the Consego Provincial of Madrid for distribution of the towns surrounding it, and One waggon to the Gobernadores of Murcia, Jaen, Cuidad Real, Cuencea, Albeacete, Guadalajara and Valencia. We are now proceeding to distribute the other part of sugar and flour to the Colonies of children in Cataluna. As you will see, as soon as we receive the goods at the station they are immediately withdrawn and distributed. Thanking you in your efforts in favour of Republica Spain, etc....... (Sgd.) ENRIQUE SANTIAGO. 292/946/30/197